Atriplex halimus: halophyte plant as potential forage for ruminants in the arid area of South-East Algeria - Arab H.; Mehennaoui S.; Haddi M.I. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The area of El Haouche in South-East of Algeria is considered as an extremely arid zone. Chenopodiaceous shrubs (Salsola vermiculata, Sueada mollis, Atriplex halimus) and the tree Tamarix africana are endemic species grazed specially by small ruminants and dromedary in this region. The physiognomic map of the study area vegetation reveals the predominance of Atriplex halimus. This is a perennial shrub tolerates well harsh conditions. Trace elements concentrations (Cu, Fe, Mn, Zn, Cd and Pb) were measured in A. halimus. Potential intake of Cu and Zn satisfy the requirement of small ruminants. Levels of Fe were high. Mn concentrations were lower. Cd and Pb contents correspond to the background level.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)